Malnutrition in the Outcome of Wound Healing at Public Hospitals in Bahir Dar City, Northwest Ethiopia: A Prospective Cohort Study - Netsanet Fentahun; Yeabsira Anteneh; Yonatan Menber (Journal of Nutrition and Metabolism)
Background. Poor nutritional status affects the normal process of the wound healing stage. There is limited evidence regarding the association between malnutrition and wound healing in Ethiopia. Objective. To assess the association between nutritional status and wound healing progress among adult individuals who had undergone abdominal surgery at Public Hospitals, Ethiopia. Methods. A prospective cohort study was conducted on 310 adult patients who had undergone abdominal surgery from August to December 2019. Data were collected using a standardized, structured, and pretested questionnaire. Anthropometric and serum albumin measurements were used to measure nutritional status. A multivariable Cox-regression analyses model was fitted to show the association between malnutrition and wound healing and p value < 0.05 was used to declare statistical significance value. Results. The cumulative incidence rate of good wound healing was 65.5% (95% CI: 60.0–71.0). Patients who had normal preoperative body mass index (adjusted hazard ratio (AHR) = 2.22 (95% CI: 1.55–3.19)) and normal range of serum albumin level (≥3.5) (AHR = 1.56 (95% CI: 1.05–2.29)) were significantly associated with better wound healing outcomes. Conclusion. Nutritional status had a strong association with good wound healing outcomes. Therefore, nutritional status screening should be done for all adult patients before undergoing abdominal surgery to improve wound healing outcomes and reduce hospital stays.